Establishing patterns on hysteroscopy in abnormal uterine bleeding (AUB) - Deeksha Pandey; Srividya Kunamneni; Pranadeep Reddy Inukollu; Hsuan Su (Wolters Kluwer Medknow Publications, 2017)
Introduction: Pattern recognition of various phases of normal endometrium and endometrial pathologies during hysteroscopy has many advantages. It would help to triage women with AUB, so as to be selective with biopsies and curettages. Recognition of normal variant or benign lesion would reduce burden to the pathologist by decreasing the number of unnecessary sampling. It will also decreases anxiety of the patient as the report/prognostication can be instant in many cases. Material and methods: This prospective, double blind, correlation study was carried out in the teaching hospital with a sample population of 70 women presenting with AUB who underwent hysteroscopy and endometrial sampling. We identified patterns of endometrium which can used to predict six endometrial pathologies which were later correlated with the final histological diagnosis. Results: There was good correlation between hysteroscopic patterns and histopathology report, 33% of starry sky appearance correlated with atrophic endometrium, 87% of tongue shaped projections correlated with endometrial polyp, 44.4% of pebble stone appearance correlated with myomatous polyp, 50% of polypoidal pattern correlated with endometrial hyperplasia. 100% correlation was seen in strawberry appearance, pattern for secretory endometrium and cerebroid appearance which was pattern designated to endometrial carcinoma. Conclusion: Hysteroscopic pattern recognition is a useful concept to triage women who require sampling for histopathological diagnosis. Keywords: Abnormal uterine bleeding, Histopathology, Hysteroscopy, Pattern recognition